Perencanaan Sumber Daya Manusia Tenaga Kependidikan Di Universitas Pendidikan Indonesia Kampus Daerah - Iin Suartini; Syamsul Maarif; Siti Amanah (Kayon Media, 2022)
Abstract: The right planning of educational supporting staff as human resources at local campus Indonesia University of Education can improve the performance of the university. The purpose of this study is to analyze the availability of educational supporting staff with their workload and the ideal standard formulation of human resources requirements in the campus area. This research used quantitative and qualitative descriptive method, while the data used primary and secondary data. Respondents were the entire supporting educational staff accross five local campusses of Cibiru, Sumedang, Tasikmalaya, Purwakarta and Serang. Data were analyzed using simple statistics and workload analysis using full time equivalent. The study results showed that the available of educational supporting staff were still dominated by high school graduates with the field of general work equipment and those who possessed a higher education level mostly aged over 45 years old. The tendon condition was caused by ineffective work accumulation at a certain time for a certain educational personnel. The ideal standard formulation of educational supporting staff on the campus areas showed that in Cibiru campuss have already ideal number of educational staff, while in Sumedang campuss the number of educational supporting staff are exceeded the ideal number. On the other hand in Tasikmalaya, Purwakarta and Serang campuses were having a shortage of ideal supporting staff. The steps to fulfill the requirements of educational supporting staff are by recruiting educational supporting staff gradually and improve the educational supporting staff’s competence.Keyword: Full Time Equivalent (FTE), human resources management, human resources planning, mapping and structuring of human resources, workload analysisAbstrak: Perencanaan sumber daya manusia tenaga kependidikan yang tepat di universitas pendidikan Indonesia kampus daerah dapat menigkatkan kinerja universitas. Tujuan penelitian ini adalah menganalisis ketersediaan tenaga kepedidikan dengan beban kerja serta formulasi standar ideal kebutuhan tenaga kependidikan di kampus daerah. Penelitian ini menggunakan metode deskriptif kuantitatif dan kualitatif, data yang digunakan adalah data primer dan data sekunder. Responden merupakan keseluran tenaga kependidikan di lima kampus daerah yaitu Cibiru, Sumedang, Tasikmalaya, Purwakarta dan Serang. Pengolahan data menggunakan statistik sederhana dan analisis beban kerja dengan menggunakan rumus full time equivalent. Hasil penelitian menunjukan bahwa ketersediaan tenaga kependidikan masih didominasi oleh pendidikan SMA dengan bidang kerja umum perlengkapan dan yang memiliki pendidikan tinggi kebanyakan sudah berusia diatas 45 tahun. Kondisi tendik tersebut mengakibatkan terjadinya penumpukan pekerjaan pada waktu tertentu dan tenaga kependidikan tertentu. Formulasi standar ideal tendik di kampus daerah menjukan bahwa kampus Cibiru sudah ideal, Sumedang melebihi jumlah ideal dan Tasikmalaya, Purwakarta dan Serang mengalami kekurangan tenaga kependidikan. Langkah-langkah pemenuhan kebutuhan tenaga kependidikan dengan beban kerja. Kata kunci: analisis beban kerja, Full Time Equivalent (FTE), Manajemen Sumber daya manusia, perencanaan sumber daya manusia, pemetaan dan struktur sumber daya manusia,